EAD466 : Fashion styling / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2018)
This course in Fashion Styling is an elective course designed to provide students with the understanding of how to start a career styling for private clients, corporate, catwalk, photo shoots, makeovers, magazine editorials and commercial. Through methods of research, presentations, practical tasks, assignments, lectures and discussions (seminars) students will learn how to develop styling concepts, deal with clients, plan together looks for photo shoots, create make-up look and hair styles and also write articles for the media. This course is designed to provide students with an overview of all aspects of fashion styling.